Analysis of the Effectiveness of Educational Personnel Performance at the Basic Instructional Skills Improvement Service Center - Muhammad Irvan Nur Iva; Rahayu Rahayu; Herman H; Andi Asrivan; Muhammad Ibnu Kafsir Sudding (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2025)
This study aims to analyze the effectiveness of the performance of educational staff at the Center for Basic Instructional Skills Development (PEKERTI), Universitas Negeri Makassar, and to identify the factors that influence it. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and document reviews, then analyzed descriptively through the stages of data reduction, presentation, and conclusion drawing. The results indicate that the performance effectiveness of educational staff at the PEKERTI Unit is considered fairly effective, although it has not yet reached an optimal level. performance effectiveness is influenced by three groups of factors: individual factors, psychological factors, and organizational factors. The main constraint in individual factors is the limited digital technical skills. From the psychological aspect, work motivation is relatively high but not yet supported by a well-structured reward system. Meanwhile, from the organizational perspective, cross-department coordination and digital system support still need to be strengthened. Overall, improving the performance effectiveness of educational staff at the PEKERTI Unit requires synergy among the enhancement of individual competencies, the strengthening of motivation, and institutional support that is adaptive to technological developments